Family income as a source of financing microbusiness women of the Yucatán Península, México - Espinosa Atoche, Teresa de Jesús (2018)
Microfinance focuses on micro-businesses, especially those managed by women, and is an issue that is generating a broad debate in the current literature of business and management sciences, because it is considered one of the essential mechanisms to reduce the poverty rate, especially in developing countries. Despite the existence of various programs and sources of microfinance, most micro-businesses do not meet the requirements to access them. Therefore family income is becoming an alternative source of microfinance for this type of business. In this sense, the objective of this study is to analyze family incomes as an alternative microfinancing for micro-businesses, located in the Yucatan Peninsula, using a sample of 565 microenterprises for this purpose. The results show that family incomes has a significant positive impact on the microfinance of micro-businesses that are managed by women.